Comparative study of biofilm formation in tubotympanic and atticoantral ear disease - Saroj, Sanjay Kumar; Kumar, Rajesh; Aggarwal, Sushil Kumar; Banerjee, Tuhina; Chaudhary, Ashvanee Kumar; Sharma, Swati; Gupta, Deepak Kumar; Das, Subhadeep (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2021)
Background: Biofilm is an organized bacterial community that may be homogeneous or heterogeneous. It plays a significant role in the pathogenesis of chronic rhinosinusitis, chronic tonsillitis and chronic suppurative otitis media. Biofilms may explain the recurrence and recalcitrant episodes of otorrhea in chronic otitis media (COM). The objective of this study was to detect biofilm formation in chronic suppurative otitis media and compare the pattern of biofilm formation in tubotympanic and atticoantral ear diseases. Methods: This was a prospective cross sectional study at a tertiary care hospital in Varanasi, Uttar Pradesh, India. Patients included in the study ranged from 10 to 65 years of age from both the sexes and varying socioeconomic status. Samples were collected using sterile precautions in cases of tubotympanic as well as atticoantral COM. The collected samples were directly inoculated onto MacConkey and blood agar media. LisaScan® EM microtitter plate reader was used to identify the presence of biofilm. Results: The most common organism was P. aeruginosa and S. aureus followed by Moraxella catarrhalis whereas in cases with tubotympanic COM, most common organism was S. aureus. We found that, in atticoantral type of COM biofilm formation was significantly more common as compared to that in tubotympanic type of COM. Conclusions: Biofilm formation in COM is even higher when atticoantral disease is present.